Prosthetics and Techniques in Repair of Animal’s Abdominal Wall - Gamal Karrouf; Adel Zaghloul; Mohamed Abou-Alsaud; Elie Barbour; Khaled Abouelnasr (Scientifica)
The management of abdominal wall repair continues to present a challenging problem, especially in the repair of major defects. Many abdominal wall defects can be repaired by primary closure; however, if the defect is large and there is a tension on the closure of the wound, the use of prosthetic materials becomes indispensable. Many studies have been performed with various materials and implant techniques, without the comparison of their degrees of success, based on sound meta-analysis and/or inclusive epidemiologic studies. This review covered the effectiveness of recent advances in prosthetic materials and implant procedures used in repair of abdominal wall, based on biomechanical properties and economic aspects of reconstructed large abdominal wall defects and hernias in animals. The presented results in this review helped to reach treatment algorithms that could maximize outcomes and minimize morbidity.